PSYCHOPEDAGOGICAL INTERVENTION IN THE FACE OF LEARNING DIFFICULTIES - Zanotto Bonamigo, Greice (Revista Gênero e Interdisciplinaridade, 2025)
The purpose of this study was to understand and analyze the importance of psychopedagogues and their interventions in the face of learning difficulties. In this context, it is essential to conduct an assessment that allows us to understand the development processes and the paths taken in learning, considering students in an interdisciplinary manner, based on various areas of knowledge and learning, both in the school and family environments, in addition to the affective, cognitive and biological aspects. The main objective of the study was to investigate the influence of psychopedagogues on the learning difficulties manifested by children and adolescents. The research was conducted through a bibliographic review, with consultation of books by different authors specialized in the subject, in addition to research on websites, academic papers, articles and magazines. Among the materials analyzed, those that offered the most pertinent and complete answers to the topic addressed were chosen.